The Business of Sustainable Cities: Public-private partnerships for creative technical and institutional solutions - Serageldin, Ismail; Barrett, Richard; Martin-Brown, Joan. (Washington, D.C.: World Bank, 1995)
In this report, international, national, non-governmental, and public and private business and industry leaders and officials present approaches to urban energy, transportation, and solid waste services that advance environmentally sustainable development. In each case, the approach improves the quality of life in cities and presents new entrepreneurial opportunities.
"An associated event of the Second Annual World Bank Conference on Environmentally Sustainable Development. Co-sponsored by The World Bank and EarthKind and held at The World Bank, Washington, D.C, September 22-23, 1994."
Includes bibliographical references (p. 31).
ne 15/05/2018
Ref
Keywords: Urban ecology (Sociology); Sustainable development; Community development, Urban; Urban renewal; Municipal services; Public-private sector cooperation